Multichannel Retailing in Beauty Product: Understanding Customer Purchase Decisions between Offline Stores, Websites, and Augmented Reality - Nila Armelia Windasari; Halim Budi Santoso (Faculty of Computer Science Universitas Indonesia, 2022)
Augmented Reality (AR) has gained attention for online retailers as it offers customers higher telepresence and provides a unique customer experience. Using the case of Sephora Virtual Artist, this research aims to understand how AR channels affect customer purchase decisions compared to other channels, particularly in beauty products. Sephora used AR through Sephora Virtual Artist to advance its other customer channels, and we compared it with its traditional websites and offline stores. A survey was conducted on 200 female respondents in Indonesia. This study used partial least squares (PLS) to find that product information and telepresence on AR can positively affect customer purchase decisions. Surprisingly, no significant difference in purchase decisions compared to two other purchase channels, i.e., traditional websites and offline stores. This study highlights that female customer tend to focus more on the products they want to purchase rather than the technology and channel of buying.